Boosting Boosting Rigid Pavement Productivity: Lessons from Experience and Working Hours on the Bengkulu Toll Road Project - Akhmad Mujiburrokhman; Danang Purwanto; Fadhil Muhammad (Fakultas Teknik Sipil dan Perencanaan, 2025)
Rigid pavement work was a key component in toll road construction that played a strategic role in the speed of project completion. Two important internal factors that affected productivity were experience and working hours. Mismanagement of either of these factors could cause project delays. This study aimed to analyze the significance of the influence of work experience and working hours on the productivity of rigid pavement work in the Trans-Sumatra Toll Road project, Bengkulu–Lubuklinggau Section 3. The research method used was a quantitative approach with multiple linear regression analysis. Primary data were obtained from daily work reports that recorded the area of concrete coverage, working hours, and worker experience. The results of the classical assumption tests showed that the regression model met the requirements of normality, multicollinearity, and heteroscedasticity. The partial test (t-test) showed that experience had a significant positive effect on productivity (Sig. = 0.000), while working hours had a significant negative effect (Sig. = 0.021). The simultaneous test (F-test) yielded Sig. = 0.000 with an R value of 0.608, meaning that the variables of experience and working hours together influenced productivity by 60.8%. The average productivity value was recorded at 91.05 m²/hour with a high variance (variance = 391.545), which reflected the actual conditions on-site and indicated the significant influence of both external and internal factors. This finding underscored the importance of effective human resource management and optimal work schedule arrangements to enhance the performance of rigid pavement construction on toll road projects.